The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.clim.2008.03.525
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses during acute and chronic infection with hepatitis C virus

Abstract: Hepatitis C virus (HCV) induces persistent infection and causes chronic liver disease in most infected patients. Vigorous HCV-specific CD4+ and CD8+ T cell responses against HCV multiple epitopes are necessary for spontaneous viral clearance during the acute phase, but the virus appears to have multiple strategies to evade these defenses. There are relatively few studies on the role of immune responses during the chronic phase of infection. CD4+ T cell responses appear to protect against liver injury and may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 216 publications
2
48
0
7
Order By: Relevance
“…HCV is particularly successful in avoiding elimination: it is estimated that up to 80% of acute infections progress to chronicity. 1 On top of several mechanisms of interference with the type 1 interferon production and response, antigen presentation, and cellmediated immune response, 23,24 HCV also modulates ap- optosis of the infected cell. 25 We previously reported that the HCV viral proteins decrease the expression of the proapoptotic protein Bid.…”
Section: Discussionmentioning
confidence: 99%
“…HCV is particularly successful in avoiding elimination: it is estimated that up to 80% of acute infections progress to chronicity. 1 On top of several mechanisms of interference with the type 1 interferon production and response, antigen presentation, and cellmediated immune response, 23,24 HCV also modulates ap- optosis of the infected cell. 25 We previously reported that the HCV viral proteins decrease the expression of the proapoptotic protein Bid.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory events play an important role during the course of chronic hepatitis C (cHepC) (8)(9)(10). Main contributors are cytokine producing CD4+ T and CD8+ T cell proliferation, increased CD5+ B cells, IL-2, IFN-γ and TNF α (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Main contributors are cytokine producing CD4+ T and CD8+ T cell proliferation, increased CD5+ B cells, IL-2, IFN-γ and TNF α (8)(9)(10). Neutrophil lymphocyte ratio (NLR) and thrombocyte lymphocyte ratio (PLR) are used as markers of inflammation in various diseases including atherosclerotic heart and renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…6,10 The cellular immune response occurs through the cytotoxic activity of CD8 + T cells on infected hepatocytes and the immuno-modulatory and antiviral cytokine-secreting actions of the CD4 + T cells. 7 Although spontaneous viral clearance is possible, in the majority of cases the virus succeeds in evading the immune response by several mechanisms, leading to persistent infection. Chief among the evasion mechanisms is the highly mutable nature of the virus, which allows it to produce escape variants and evade recognition by cells of the adaptive immune system.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 Following HCV infection of the liver, the host's innate immune system responds via the activation of natural killer lymphocytes and the production of type I and III interferons. [7][8][9] The adaptive humoral response involves the production of neutralizing antibodies that may block viral entry into healthy hepatocytes by targeting the viral envelope's structural proteins E1 and E2. 6,10 The cellular immune response occurs through the cytotoxic activity of CD8 + T cells on infected hepatocytes and the immuno-modulatory and antiviral cytokine-secreting actions of the CD4 + T cells.…”
Section: Introductionmentioning
confidence: 99%